A meta‐analysis on the prevalence of chronic kidney disease in liver transplant candidates and its associated risk factors and outcomes. (7th December 2021) - Teo, Vanessa Xin Yi; Heng, Ryan Rui Yang; Tay, Phoebe Wen Lin; Ng, Cheng Han; Tan, Darren Jun Hao; Ong, Yuki; Tan, En Ying; Huang, Daniel; Vathsala, Anantharaman; Muthiah, Mark; Tan, Eunice Xiang Xuan
Summary: Pre‐liver transplant (LT) chronic kidney disease (CKD) has emerged as a leading cause of post‐operative morbidity. We aimed to report the prevalence, associated risk factors, and clinical outcomes in patients with pre‐LT CKD. Meta‐analysis and systematic review were conducted for included cohort and cross‐sectional studies. Studies comparing healthy and patients with s pre‐LT CKD were included. Outcomes were assessed with pooled hazard ratios. 15 studies were included, consisting of 82, 432 LT patients and 26, 754 with pre‐LT CKD. Pooled prevalence of pre‐LT CKD was 22.35% (CI: 15.30%–32.71%). Diabetes mellitus, hypertension, viral hepatitis, and non‐alcoholic fatty liver disease, and older age were associated with increased risk of pre‐LT CKD: (OR 1.72 CI: 1.15–2.56, P = 0.01), (OR 2.23 CI: 1.76–2.83, P < 0.01), (OR 1.09; CI: 1.05–1.13, P < 0.01), (OR 1.73; CI: 1.10–2.71 P = 0.03), and (MD: 2.92 years; CI: 1.29–4.55years; P < 0.01) respectively. Pre‐LT CKD was significantly associated with increased mortality (HR 1.38; CI: 1.2–1.59; P < 0.01), post‐LT end‐stage renal disease and post‐LT CKD. Almost a quarter of pre‐LT patients have CKD and it is significantly associated with post‐operative morbidity and mortality. However, long‐term outcomes remain unclear due to a lack of studies reporting such outcomes. Abstract : Pre‐liver transplant (LT) chronic kidney disease (CKD) has emerged as a leading cause of post‐operative morbidity. We aimed to report the prevalence, associated risk factors and clinical outcomes in patients with pre‐LT CKD